Structural changes in world crude oil trade: Increased government involvement and implications for consuming countries - Jochen H. Mohnfeld (Intereconomics, 1980)
The way in which international trade in crude oil is conducted has changed drastically since the beginning of 1979. Who has access to crude oil in producing countries, in what quantity, at what prices, and for how long is in question. Jochen Mohnfeld analyses, recent trends and future developments, paying special regard to the producer countries' tendency to require more state involvement of importing countries in crude oil trade and drawing some tentative conclusions for the latter's energy policies.
Keywords: 330; Oil Markets